Residual tricuspid regurgitation after tricuspid transcatheter edge-to-edge repair: insights into the EuroTR registry - Stolz, Lukas; Kresoja, Karl-Patrik; Stein, Jennifer von; Fortmeier, Vera; Koell, Benedikt; Rottbauer, Wolfgang; Kassar, Mohammad; Goebel, Bjoern; Denti, Paolo; Achouh, Paul; Rassaf, Tienush; Barreiro-Perez, Manuel; et al. (European journal of heart failure, 2024)
Aims Data on the prognostic impact of residual tricuspid regurgitation (TR) after tricuspid transcatheter edge-to-edge repair (T-TEER) are scarce. The aim of this analysis was to evaluate 2-year survival and symptomatic outcomes of patients in relation to residual TR after T-TEER. Methods and results Using the large European Registry of Transcatheter Repair for Tricuspid Regurgitation (EuroTR registry) we investigated the impact of residual TR on 2-year all-cause mortality and New York Heart Association (NYHA) functional class at follow-up. The study further identified predictors for residual TR ≥3+ using a logistic regression model. The study included a total of 1286 T-TEER patients (mean age 78.0 ± 8.9 years, 53.6% female). TR was successfully reduced to ≤1+ in 42.4%, 2+ in 40.0% and 3+ in 14.9% of patients at discharge, while 2.8% remained with TR ≥4+ after the procedure. Residual TR ≥3+ was an independent multivariable predictor of 2-year all-cause mortality (hazard ratio 2.06, 95% confidence interval 1.30-3.26, p = 0.002). The prevalence of residual TR ≥3+ was four times higher in patients with higher baseline TR (vena contracta >11.1 mm) and more severe tricuspid valve tenting (tenting area >1.92 cm2). Of note, no survival difference was observed in patients with residual TR ≤1+ versus 2+ (76.2% vs. 73.1%, p = 0.461). The rate of NYHA functional class ≥III at follow-up was significantly higher in patients with residual TR ≥3+ (52.4% vs. 40.5%, p < 0.001). Of note, the degree of TR reduction significantly correlated with the extent of symptomatic improvement (p = 0.012). Conclusions T-TEER effectively reduced TR severity in the majority of patients. While residual TR ≥3+ was associated with worse outcomes, no differences were observed for residual TR 1+ versus 2+. Symptomatic improvement correlated with the degree of TR reduction.
Gesehen am 13.02.2025